2020
DOI: 10.1080/19396368.2020.1753850
|View full text |Cite
|
Sign up to set email alerts
|

The limited knowledge of placental damage due to neglected infections: ongoing problems in Latin America

Abstract: The placenta works as a selective barrier, protecting the fetus from potential infections that may affect the maternal organism during pregnancy. In this review, we will discuss several challenging infections that are common within Latin American countries and that may affect the maternal-fetal interface and pose risks to fetal development. Specifically, we will focus on emerging infectious diseases including the arboviruses, malaria, leishmaniasis, and the bacterial foodborne disease caused by Shiga toxinprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 180 publications
(217 reference statements)
0
7
0
Order By: Relevance
“…Viruses and fungi are also associated with the development of chorioamnionitis, such as CMV, enterovirus, human papillomavirus (HPV), Zika virus and other arboviruses, and Candida spp. [ 162 ].…”
Section: The Influence Of Gestational Diseasesmentioning
confidence: 99%
“…Viruses and fungi are also associated with the development of chorioamnionitis, such as CMV, enterovirus, human papillomavirus (HPV), Zika virus and other arboviruses, and Candida spp. [ 162 ].…”
Section: The Influence Of Gestational Diseasesmentioning
confidence: 99%
“…Recently, an increasing number of cases of DENV infection during pregnancy have been reported and are definitely associated with increased morbidity and mortality in both mothers and fetuses. 2 , 3 , 4 Meta-analysis showed that preterm birth and low birth weight are the most common adverse pregnancy outcomes associated with maternal DENV infection. 5 , 6 Further histopathological examinations of placentas collected at delivery from maternal DENV infection have shown hypoxic lesions with villous stromal edema and infarcted and preinfarcted areas in 19 of 24 cases, including eight from mothers who did not report overt shock syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnant women, cell-mediated immunity is modulated to promote the development of the placenta and its implantation in the maternal endometrium. But this halt in cell-mediated immunity makes pregnant women more susceptible to intracellular pathogens [25]. However, in malaria-infected pregnant women, an increase in cell-mediated immunity has been observed in the local placental environment with elevated levels of pro-in ammatory cytokines, such as IFN-γ, IL-2, and TNF-α [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…But this halt in cell-mediated immunity makes pregnant women more susceptible to intracellular pathogens [25]. However, in malaria-infected pregnant women, an increase in cell-mediated immunity has been observed in the local placental environment with elevated levels of pro-in ammatory cytokines, such as IFN-γ, IL-2, and TNF-α [25][26][27]. These cytokine levels correlate with increased Hofbauer cell density, parasite density, and malaria pigments in the placenta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation